Pengawasan Praktik – Praktik Audit Syariah terhadap Tingkat Kepercayaan Stakeholder pada Perbankan Syariah di Indonesia - Vita Citra Mulyandini; Adelia Nidayanti (Badan Penerbit Fakultas Ekonomi dan Bisnis Universitas Singaperbangsa Karawang, 2023)
This study aims to examine the influence of supervision of sharia audit practices on the level of stakeholder trust in Islamic banking in Indonesia. Supervision of sharia audit practices is measured through three dimensions, namely auditor independence, auditor competence, and auditor integrity. Meanwhile, the level of stakeholder trust is measured using three variables, namely customer trust, shareholder trust, and government trust. This study used a quantitative approach with a survey method and data was collected through questionnaires distributed to 173 respondents. The results of the study show that auditor independence, auditor competence, and auditor integrity have a significant positive effect on customer and shareholder trust. Meanwhile, only auditor independence and auditor integrity have a significant effect on stakeholder trust. In addition, the results of the regression test also show that supervision of sharia audit practices as a whole has a significant positive effect on stakeholder trust in Islamic banking in Indonesia. This research contributes to the development of knowledge about sharia auditing practices and the level of stakeholder confidence in sharia banking in Indonesia. The results of this study can be input for regulators and the Islamic banking industry in improving Islamic audit practices and increasing the level of stakeholder confidence in Islamic banking in Indonesia.